Thermal Stability Of Laser Treated Die Material For Semi-Solid Metal Forming - S. N., Aqida; Maurel, M; Brabazon, D.; Naher, Sumsun; Rosso, M (Springer Link, 2009)
This paper presents laser surface modification work performed to improve the lifetime of die materials. Die material AISI H13, with typical hardness in the range of 42 to 48 HRC, offers high wear and corrosion resistance. However the cyclic high temperature conditions along with exposure to high viscosity molten metal in semi6solid forming cause the die to wear and crack with resultant shortened die lifetime. In this study, the thermal stability of die material at elevated temperature was investigated through micro6hardness testing and a metallographic study. AISI H13 samples were laser glazed using CO2 continuous wave mode laser with 10.6 9m wavelength. Samples were attached to a specially designed rotating chuck to enable it to be rotated at speeds up to 1500 rpm and allow flat surface glazing to take place. The microhardness was measured for as6glazed samples and annealed samples which were held at temperatures ranging from 550oC to 800oC with 50oC intervals. The metallographic study conducted examined the formation of three zones at different depths which were the glazed zone, the heat affected zone and the substrate. As a result of rapid heating and cooling from the laser glazing process, a metallic glass layer was developed which exhibited an average micro6hardness of 900 HV when exposed to 3.34E+10 W/m2 laser irradiance within a range of 3.64 to 5.66 ms exposure time. Crystallization in glazed zone increased as the annealing temperature increased. As the annealing temperature reached above approximately 600oC, the microhardness decreased to approximately 600 HV (equivalent to approx. 54 HRC) due to local crystallization. These findings show potential direct application of glazed dies for non6ferrous semisolid forming and the requirement for thermal barrier protection for application at higher temperatures.